What makes a query temporally sensitive?. Issue 1 (27th December 2016) - Willis, Craig; Sherman, Garrick; Efron, Miles
ABSTRACT: This work examines factors that affect manual classifications of "temporally sensitive" information needs. We introduce the concepts of temporal relevance and temporal topicality to differentiate between different aspects of temporal retrieval research. We use qualitative and quantitative techniques to analyze 660 topics from the Text Retrieval Conference (TREC) previously used in the experimental evaluation of temporal retrieval models. We use regression analysis to model previous manual classifications. We identify factors and potential problems with previous classifications, proposing principles and guidelines for future work on the evaluation of temporal retrieval models.